Usefulness of plateletcrit in the prediction of major adverse cardiac and cerebrovascular events in patients with carotid artery stenosis. (October 2019) - Aslan, Serkan; Demir, Ali Rıza; Demir, Yusuf; Taşbulak, Ömer; Altunova, Mehmet; Karakayalı, Muammer; Yılmaz, Emre; Gürbak, İsmail; Ertürk, Mehmet
Objectives: Platelets play an important role in the pathogenesis of atherosclerosis and the physiopathology of cardiovascular events. Plateletcrit provides complete information on total platelet mass. The relationship between plateletcrit values and long-term outcomes in patients with carotid stenosis is not known. The purpose of the present study is to evaluate the reliability of plateletcrit for predicting major adverse cardiac and cerebrovascular events (MACCE) in patients with carotid stenosis. Methods: A total of 230 patients with more than 50% stenosis of the carotid artery were retrospectively included in this study. All cases were divided into two groups according to the calculated threshold value of plateletcrit with receiver operating characteristics curve and baseline parameters and clinical outcomes were compared. Univariate and multivariate analyses were used to evaluate the association between the plateletcrit and MACCE. Results: The cut-off value for plateletcrit was found to be 0.233 for predicting MACCE, with 56.2% sensitivity and 68.0% specificity. High plateletcrit levels were demonstrated to be statistically higher in patients with MACCE (0.247 in the MACCE (+) group vs. 0.213 in the MACCE (–) group, p  < 0.001). In the Kaplan–Meier survival analysis, the long-term mortality rate was higher in the high plateletcrit group ( p  = 0.006). Multivariate regression analysis showed that plateletcrit was independently associated with MACCE (OR: 2.196, CI: 1.200–4.018; p  = 0.011). Conclusions: Our data suggest that plateletcrit has an independently predictive value for long-term mortality and MACCE, and it can be used as a marker to predict the long-term adverse outcomes in patients with carotid stenosis.